Preferensi Kecoa Amerika Periplaneta americana (L.) (Blattaria: Blattidae) terhadap Berbagai Kombinasi Umpan - HERMA AMALIA; IDHAM SAKTI HARAHAP (Jurnal Entomologi Indonesia, 2010)
Currently, most cockroach control in urban environment relies on bait application. Aversion of some commercial bait by cockroach cause failure to control cockroach problems. Developing local bait can improve this situation. This research was aimed to find proper combination of some cockroach diet to be formulated in effective bait. Research was conducted in Department of Plant Protection, Bogor Agricultural University, since November 2007-March 2008. Combination of peanut butter, chicken egg, and strawberry jam seem to be a candidate of effective bait for local cockroach.